Identification of the KIR3DL1*0050105 allele by sequence-based techniques. - Wang, L; Yindom, L; Rowland-Jones, S; Dong, T (2014)
KIR3DL1*0050105 differs from KIR3DL1*0050101 with two nucleotide substitutions at 6709(C > T) and 13398 (G > A) in introns 5 and 7, respectively.